Pharmaco epidemiology of drugs used in post-cataract surgery patients in tertiary care hospital - Hiremath, Geetanjali; Masare, Pankajkumar; Kotinatot, Basavaraj C. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In India cataract is the principal cause of blindness responsible for 62.6% as per national programme for control of blindness survey and as per our knowledge, very few systematically analysed data are available on the drug utilization study pattern of medical intervention for post cataract surgery in India. Hence, the present study was under taken to generate baseline drug use data and analyse various aspects of drug prescribing practices. Methods: This study was conducted in department of ophthalmology BIMS Belagavi. A total of 449 patients’ prescription was analysed prospectively. The data was analysed statistically, and results were expressed as numbers and percentage. Results: A total of 2306 drugs were prescribed for 449 patients who underwent cataract surgery. All patients received topical eye drops includes bromfenac 0.1% eye drop and other one is a fixed drug combination of dexamathasone 0.1% plus ofloxacin 0.3% eye drop. Use of antibiotic in association with sex found to be significant (p- value <0.004). Average number of drugs per prescription was 5.1 and drugs which prescribed in generic name were 60.99% and overall percentage of drugs prescribed by brand name was 38.94% which includes 100% eye drops were prescribed by brand names. Fixed drug combination includes 19.50% and drugs from essential drug list used were 80.49%. Conclusions: Health care providers have to take initiative for rational prescribing keeping in mind that it is not only a matter of national policy but also to wellbeing of individual patient.